Regional Flaps Accessible to Everyone: Regional Reconstruction Revisited. (2nd September 2014) - Patel, Urjeet; Hanasono, Matthew M.; Richmon, Jeremy D.; Hartig, Gregory K.; Lin, Derrick T.
Abstract : Program Description: The miniseminar will address regional reconstruction of the head and neck, with attention to surgical options available to the general otolaryngologist–head and neck surgeon. The format will include a descriptive portion of both longstanding and emerging reconstructive flap options that are commonly used today. The remainder will be case based, with depiction of commonly encountered wounds or defects followed by an interactive forum to discuss surgical and/or medical strategies for wound management. Audience participation will be encouraged through the Audience Response System to discuss preferred surgical strategies. Educational Objectives: (1) Describe recent advances of commonly used regional flaps for head and neck reconstruction: pectoralis, submental, supraclavicular flaps, temporoparietal, facial artery mucosal muscle, and trapezius. (2) Cite the indications and contraindications for each flap, with consideration of location and size of defect, mobility, and prior irradiation. (3) Incorporate the information provided to develop an algorithmic approach to wound management using regional flaps with awareness of their use and limitations.